Konsep Dasar Kepemimpinan dalam Pendidikan Islam - Salsabila Nahdiaturrosidah; Sulistyorini; Nur Efendi (STIKes Ibnu Sina Ajibarang, 2025)
Leadership in Islamic education is an important aspect aimed at forming a generation that is not only intellectually intelligent but also strong in faith and morals. The basic concept of leadership in this context includes several key aspects, namely leadership based on Islamic values, noble character, and educational goals. Leaders in Islamic education are expected to serve as role models for students, implement the principle of shura (consultation) in decision-making, and emphasize the importance of beneficial knowledge. The purpose of this research is to understand the principles of leadership in Islamic education derived from the Qur'an and Hadith. Data was collected through literature studies and document analysis. The results of the research indicate that leadership in Islamic education must be based on Islamic principles such as honesty, justice, and wisdom. Islamic education leaders are responsible for guiding students towards optimal self-development, both academically, morally, and spiritually. The conclusion of this research shows that the concept of leadership in Islamic education must combine modern leadership principles with spiritual and ethical values of Islam to create a good leadership model. This research provides insights into the basic concepts of leadership in Islamic education.